Establishment of analytical methods for allergenic compounds in mouthwashes and sanitary napkins by ultra-high-performance liquid chromatography with tandem mass spectrometry - Sim, Hee Jung; Jeong, Hee Jin; Lee, Yeong In; Cho, Yu Jin; Baek, Seung Hoon; Kim, Jong Hwan (Analytical Science and Technology, 2023)
Analytical methods for detecting atranol, chloroatranol, evernic acid, (+)-usnic acid, and atranorin in sanitary napkins and mouthwashes were developed using ultrahigh performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). UHPLC-MS/MS conditions were optimized for rapid, sensitive, and simultaneous analysis of the five allergenic compounds. The methods were validated by assessing their specificity, matrix effects, limit of detection (LOD), limit of quantification (LOQ), linearity, accuracy, and precision. Good linearity was achieved with a determination coefficient of ≥0.99. The LOD and LOQ were 2.1-9.8 and 6.4-29.6 ng/g for sanitary napkins and 0.29-0.48 and 0.87-1.45 ng/mL for mouthwashes, respectively. The accuracy and precision were within an acceptable range according to the criteria reported in the European SANTE/11813/2017 guidelines (70-120 % recovery, <20 % relative standard deviation). Therefore, these methods can be used to analyze atranol, chloroatranol, evernic acid, (+)-usnic acid, and atranorin in sanitary napkins and mouthwashes.
Keywords: allergenic compounds #1; method validation #5; mouthwash #2; sanitary napkins #3; tandem mass spectrometry #4